Enhancing Safety: A Smart Baby Monitoring System for Deaf Parents (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
This study presents a multimodal baby monitoring system designed to address the accessibility gap for deaf parents. The system integrates acoustic analysis (300–600 Hz frequency range) with synchronous visual (OLED) and haptic (vibration motor) alerts, achieving 98.1% cry detection accuracy and ≤7.6% false alarms in controlled testing. A dual-stage architecture combines an Arduino-based sound sensor (MAX9814 microphone) with Bluetooth 4.0 (HC-05) wireless transmission, enabling real-time notifications within a 10-meter range. Experimental validation under varying noise conditions (30–70 dB SNR) demonstrated consistent performance, with spectral analysis effectively discriminating baby vocalizations from adult speech (80–300 Hz) and environmental noise. The prototype’s compact mechanical design (10×5×2 cm) prioritizes usability, offering an inclusive solution that bridges the limitations of audio-dependent commercial monitors. Future work will explore Wi-Fi integration and AI-enhanced cry classification for improved robustness.